(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Melamine is a key organic chemical intermediate with a wide range of uses. The main use of melamine in the wood industry is more than 70% of the total consumption. The development of this industry is determined by the availability of domestic market capacity and the ever-increasing demand for this product. Melamine paint in the industry and plastic work in release the most important raw materials. Products based on melamine-formaldehyde are used for paper production and furniture. Melamine is also widely used in electrical engineering and textiles. Such widespread use has led to rapid growth in melamine production worldwide.